An epidemic model with density dependent parameters and vaccination - Q. J. A. Khan; B. S. Bhatt (International Journal of Mathematics and Mathematical Sciences)
A model originally suggested by Greenhalgh [12] and later modified by that same author [13,14] is considered under the assumption that the transmission coefficient is inversely proportional to the total population size. The purpose of this study is to see the effect of this density dependent transmission coefficient on the stability criteria for the equilibrium of the model equations. It is found that Greenhalgh’s results are still valid.